DETERMINING THE RESERVES FOR REDUCING THE COST OF LIVESTOCK PRODUCTS AND IMPROVING THE QUICK ANALYSIS METHOD (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The article studies methods for determining and express analyis of reserves for reducing the cost of livestock products. A conclusion was formulated and proposals were made to reduce